KELAYAKAN BUKU SANTUN BERBAHASA UNTUK PENGASUHAN BERBAHASA PESERTA DIDIK TK DI KABUPATEN KUDUS - Ristiyani Ristiyani; Mila Roysa; Fina Fakhriyah (Universitas Muria Kudus, 2017)
The purpose of this study was to measure the feasibility of well mannered language book for parenting the preschool-aged children in Kudus regency. Based on feasibility test that had been executed, it was obtained feasibility test score from linguist with feasibility aspect of writing, feasibility of content, feasibility of language use, feasibility of presentation, and feasibility of graph, it was obtained result equal to 78,3% which meant in feasible category. 83.5% score was obtained from the feasibility test of the material expert with the aspect of the feasibility of the grammar, the feasibility of the content, the feasibility of language use, the feasibility of presentation, and the feasibility of graph which meant in the very feasible category. Feasibility test from module expert with aspect of grammar, content feasibility, feasibility of language use, feasibility of presentation, and feasibility of graph, it was obtained the score of 90% in very feasible category. Based on these data, it could be concluded that the well mannered language book that had received input of the linguists experts, materials (psychologists), and teachers was very feasible in the category.